2011
DOI: 10.1155/2011/863734
|View full text |Cite
|
Sign up to set email alerts
|

Recent Applications of Liposomes in Ophthalmic Drug Delivery

Abstract: Liposomal formulations were significantly explored over the last decade for the ophthalmic drug delivery applications. These formulations are mainly composed of phosphatidylcholine (PC) and other constituents such as cholesterol and lipid-conjugated hydrophilic polymers. Liposomes are biodegradable and biocompatible in nature. Current approaches for topical delivery of liposomes are focused on improving the corneal adhesion and permeation by incorporating various bioadhesive and penetration enhancing polymers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
100
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(103 citation statements)
references
References 74 publications
2
100
0
1
Order By: Relevance
“…Over the past decade, liposomal drug delivery systems were used by many researchers and various applications were reported, such as targeted gene therapy [11,25], transfollicular [15] or ophthalmic [20] drug delivery. In many cases DOPE (dioleoyl phosphatidylethanolamine), an analogue of the native PE with a defined fatty acid composition, was used in liposomal formulations.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, liposomal drug delivery systems were used by many researchers and various applications were reported, such as targeted gene therapy [11,25], transfollicular [15] or ophthalmic [20] drug delivery. In many cases DOPE (dioleoyl phosphatidylethanolamine), an analogue of the native PE with a defined fatty acid composition, was used in liposomal formulations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the major limitation with topical liposomes is the lack of sustained efficacy, due to biological barriers in the eye and clearance from tear dilution. 7 Different routes of injectable liposome systems tested include periocular, intravitreal, and subconjunctival. 28,29 Moreover, recent reports have shown the benefits of subconjunctival injections with improved absorption rates and sustained efficacy, using low molecular weight heparin, 30 streptokinase, and clodronate.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Latanoprost, a lipophilic drug usually delivered in the form of an oil/water emulsion (Xalatan Liposomes, which have been shown to be biocompatible nanocarriers for ocular use, allows for delivery of both the lipophilic drug molecule as well as its hydrophilic active products, due to its physical structure of a polar core and lipophilic bilayer. 7 Liposomal encapsulation protects drug molecules from enzymatic hydrolysis in the physiological environment while in circulation, and thus increases stability. Previous studies on topical application of liposomes demonstrated poor penetration into the eye, [8][9][10][11] however, while studies on subconjunctival injections on other IOP-lowering drugs showed limited sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…For example, liposomes prepared with DSPE‐PEG 2000 and helper lipids were a popular kind of nonviral ocular gene carrier 20, 21. DSPE‐PEG 2000 contained liposomes with conjugated cRGD ligand were proved to be efficient vectors for retinal cells when loaded with VEGF‐siRNA 22, 23.…”
Section: Introductionmentioning
confidence: 99%